Assessment of microstructural abnormalities in gray and white matter of minimal hepatic encephalopathy patients using diffusion kurtosis imaging and their associations with neurocognitive dysfunction - Sun, Qing; Fan, Wenliang; Liu, Yuan; Kou, Zhifeng; Han, Ping (Frontiers in Human Neuroscience, 2025)
AimsAlthough neural activity abnormalities have been reported in cirrhosis patients with minimal hepatic encephalopathy (MHE), the neurophysiological mechanisms underlying microstructural brain alterations remain poorly understood. This prospective study aimed to assess microstructural abnormalities in both gray matter and white matter of MHE patients by using diffusion kurtosis imaging (DKI), and to examine associations between these alterations and neurocognitive and clinical measurements.MethodsThirty-one Hepatitis B Virus-related cirrhotic patients without MHE (NMHE), thirty Hepatitis B Virus-related cirrhotic patients with MHE, and 59 gender-, age-, education-matched healthy controls underwent diffusional kurtosis imaging and neurocognitive assessments. We used tract-based spatial statistics (TBSS) analysis to estimate group differences of white matter (WM) microstructure and voxel-based morphometry analysis to determine gray matter (GM) abnormalities. Correlation analyses were further performed to assess relationships between altered diffusional parameters and clinical variables, such as neurocognitive performances and disease duration.ResultsThe TBSS analysis results showed that MHE patients had significantly decreased fractional anisotropy (FA) in the temporal part of the left superior longitudinal fasciculus and decreased kurtosis fractional anisotropy (KFA) in the left corticospinal tract and anterior thalamic radiation (p < 0.05, threshold-free cluster enhancement corrected). Notably, lower KFA in WM regions correlated with worse neurocognitive test scores in MHE patients. For GM, MHE patients exhibited increased volume of thalamus. No significant WM or GM differences were observed between NMHE patients and the other two groups.ConclusionMinimal hepatic encephalopathy patients demonstrated microstructural abnormalities in both WM and GM, predominantly affecting regions involved in cognitive, attention, and motor functions. These findings suggest that disruption of microstructural integrity may underlie the pathophysiological underpinnings of neurocognitive dysfunction in MHE, offering neuroimaging evidence for disease mechanisms.